La gestión de programas académicos desde la perspectiva de la gestión del conocimiento apoyada con esquemas preconceptuales (2014)
Unification of academic program processes and goals is still far from the state of the art. Such unification can be reached by using knowledge management processes. For this reason, in this paper we propose a revisited version of a previous pre-conceptual-schema-based representation of the academic programs. We design a survey directed to experts and we obtain several responses. The resulting pre-conceptual schema is exemplified by using the system engineering program belonging to the Universidad de Medellín.